2016
DOI: 10.4103/0972-5229.186221
|View full text |Cite
|
Sign up to set email alerts
|

Early demographic and clinical predictors of developing acute kidney injury in snake bite patients: A retrospective controlled study from an Indian tertiary care hospital in North Eastern Uttar Pradesh India

Abstract: Aims:This study was conducted retrospectively to define early demographic and clinical predictors for acute kidney injury (AKI) among snake bite patients at the time of hospital admission.Materials and Methods:We analyzed 138 cases with a poisonous snake bite. Patients were classified into two groups according to the presence and absence of AKI. The data regarding clinical features and demographic profile of these patients were collected from the hospital records in a prestructured pro forma and statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
2
6
1
Order By: Relevance
“…Cellulitis was 39%-98.7%[20,23-26,28-30] as compared to that of 13.6% observed in our study, hypotension of 4.5% observed in current study as compared to that of 6.3%-45.2% in other studies[9,20,23,24,27,29,30], neurotoxicity of 5.7% as compared to that of 3.2%-100% in other studies[11,23,25,28,29]. Bleeding/coagulopathy which is a major symptom of systemic viper poisoning was observed in 88.6% patients as compared to 27.8%-65.8% in other studies of snake bite-induced AKI[11,20,23-26,28-30].…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Cellulitis was 39%-98.7%[20,23-26,28-30] as compared to that of 13.6% observed in our study, hypotension of 4.5% observed in current study as compared to that of 6.3%-45.2% in other studies[9,20,23,24,27,29,30], neurotoxicity of 5.7% as compared to that of 3.2%-100% in other studies[11,23,25,28,29]. Bleeding/coagulopathy which is a major symptom of systemic viper poisoning was observed in 88.6% patients as compared to 27.8%-65.8% in other studies of snake bite-induced AKI[11,20,23-26,28-30].…”
Section: Discussioncontrasting
confidence: 46%
“…In various studies, the symptoms of oligoanuria has been reported to be 13.8%-100%[9,11,20,21,23,24,26,28,30] and hematuria/black colored urine 24.6%-80%[9,11,20,22,24,26,29] as compared to that of 79.5% and 54.5% respectively in our study. Cellulitis was 39%-98.7%[20,23-26,28-30] as compared to that of 13.6% observed in our study, hypotension of 4.5% observed in current study as compared to that of 6.3%-45.2% in other studies[9,20,23,24,27,29,30], neurotoxicity of 5.7% as compared to that of 3.2%-100% in other studies[11,23,25,28,29].…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…The reported prevalence rates of AKI following haemotoxic envenomation vary from 14 to 44% [ 4–8 , 15 ]. Relatively higher AKI prevalence rates have been reported by studies that have employed both urine output and creatinine-based criteria for the diagnosis of AKI, compared with studies that have employed creatinine-based criteria alone [ 5 , 8 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was the consequence of antivenom inaccessibility, the cost of which (42,000 FCFA or US $ 70 per vial) representing several months of income for a Beninese farmer. The critical threshold of treatment delay was estimated by many authors below 2 hours after snakebite [ 20 , 48 , 49 , 53 ]. However, Alves et al [ 54 ] reported that 58% of the AKIs in their series were admitted to hospital less than 3 hours after the bite -meaning that early treatment was unable to prevent AKI-, and Ratnayake et al [ 45 ] did not show any difference according to treatment time between patients without AKI and those with AKI whatever the severity.…”
Section: Discussionmentioning
confidence: 99%